Commentary for Addressing the Multiple Behavioural Risk Factors: A Call for Integrated Adolescent Health Interventions - Aprezo Pardodi Maba (Bulletin of Counseling and Psychotherapy, 2025)
Adolescents worldwide are facing an alarming convergence of four lifestyle-related behavioural risks – physical inactivity, sedentary behaviour, poor sleep, and unhealthy diet – that threaten their current and future wellbeing. These behaviours frequently co-occur and are strongly associated with a range of adverse outcomes, including physical and mental health issues and compromised academic performance. Emerging evidence suggests these risks are particularly concerning in Southeast Asia, particularly Indonesia.